2016
DOI: 10.1021/acs.jafc.6b00761
|View full text |Cite
|
Sign up to set email alerts
|

Iron (Fe2+)-Catalyzed Glucosamine Browning at 50 °C: Identification and Quantification of Major Flavor Compounds for Antibacterial Activity

Abstract: Glucosamine browning at 50 °C with (GlcN/Fe(2+)) or without iron (GlcN) was studied over time from 0 to 48 h. Generation of reactive oxygen species (ROS), H2O2, and (1)O2, along with α-dicarbonyls, fructosazine, and deoxyfructosazine, was evaluated. Singlet oxygen generation increased over time and was greater in GlcN/Fe(2+) caramel solution. The presence of iron significantly increased the concentration of α-dicarbonyls at an early incubation time (3 h). Fructosazine and deoxyfructosazine were the major degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 47 publications
(92 reference statements)
1
54
0
Order By: Relevance
“…Other works has demonstrated alterations of specific virulence regulators of known food pathogens when in the presence of model MRPs [36]. Accelerated non-enzymatic browning reaction, using a glucosamine/Fe 2+ complex to generate singlet oxygen and reactive alpha dicarbonyls, will lower MIC 50 values against heat-resistant E.coli at acidic rather than neutral pH [30]. High molecular weight (>10 kDa) melanoidins have also been identified as active MRPs with effective antimicrobial activity that have the potential to induce irreversible damage of cell membrane permeability and function [12,20].…”
Section: Can Mrps Replace Traditional Chemical Antimicrobial Agents?mentioning
confidence: 99%
See 2 more Smart Citations
“…Other works has demonstrated alterations of specific virulence regulators of known food pathogens when in the presence of model MRPs [36]. Accelerated non-enzymatic browning reaction, using a glucosamine/Fe 2+ complex to generate singlet oxygen and reactive alpha dicarbonyls, will lower MIC 50 values against heat-resistant E.coli at acidic rather than neutral pH [30]. High molecular weight (>10 kDa) melanoidins have also been identified as active MRPs with effective antimicrobial activity that have the potential to induce irreversible damage of cell membrane permeability and function [12,20].…”
Section: Can Mrps Replace Traditional Chemical Antimicrobial Agents?mentioning
confidence: 99%
“…The antibacterial activity could therefore be provided by the generation of a hydroxyl radical from the Fenton Reaction that involves ferrous ion interacting with hydrogen peroxide. Recently, glucosamine browning in the presence of ferrous ion displayed antimicrobial activity towards heat resistant at pH 5, but not pH 7, thus showing the importance of maintaining ferrous ion solubility to initiate reactivity with nonenzymatic browning precursors that generate alpha dicarbonly and hydrogen peroxide byproducts; candidates for the observed antimicrobial activity [30].…”
Section: Proposed Antimicrobial Mechanisms Of Mrpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gottardi et al (2014) came to the same conclusion and reported that GlcN-glycated gluten hydrolysates could inhibit the growth of E. coli at 40 mg/mL, but not B. subtilis . It is expected that these antimicrobial activities are not only due to the glycopeptides alone, but also due to other chemical compounds produced, including GlcN-derived α-DCs and the GlcN self-condensation products fructosazine and deoxyfructosazine (Hrynets et al, 2016; Bhattacherjee et al, 2016). Indeed, recent studies have shown that fructosazine was able to inhibit 50% of the growth of extremely heat-resistant E. coli AW 1.7 at 3.6 g/L at pH 5 (Hrynets et al, 2016; Bhattacherjee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that these antimicrobial activities are not only due to the glycopeptides alone, but also due to other chemical compounds produced, including GlcN-derived α-DCs and the GlcN self-condensation products fructosazine and deoxyfructosazine (Hrynets et al, 2016; Bhattacherjee et al, 2016). Indeed, recent studies have shown that fructosazine was able to inhibit 50% of the growth of extremely heat-resistant E. coli AW 1.7 at 3.6 g/L at pH 5 (Hrynets et al, 2016; Bhattacherjee et al, 2016). Here fructosazine exerted its antimicrobial action by permeabilizing the cell membrane, damaging membrane integrity and fragmenting DNA.…”
Section: Introductionmentioning
confidence: 99%